Visualization of diesel spray and combustion from lateral side of two-dimensional piston cavity in rapid compression and expansion machine, second report: Effects of injection pressure and interval of split injection. (March 2022) - Fan, Chengyuan; Nishida, Keiya; Ogata, Yoichi
The effect of split injection on the fuel spray and combustion processes in a rapid compression and expansion machine was investigated using the visualization process. A two-dimensional piston cavity, designed with the cross section of a reentrant piston, was installed in the combustion chamber to observe the combustion process from the lateral side. Combustion experiments were conducted with injection pressures of 80 MPa, 120 MPa, and 180 MPa and an O2 concentration of 15%. The spray/wall interaction, mixture distribution, and ignition location were investigated using the shadow method. Along with natural flame luminescence, different spray impinging behaviors on combustion process were studied. Furthermore, the combustion characteristics of in-cylinder pressure, apparent heat release rate, and combustion phase were recorded and analyzed simultaneously. The results showed that both high injection pressure and split injection with a longer interval effectively improved the combustion performance. In addition, when the pilot injection was advanced further, the injection interval had a larger influence in reducing soot generation, while the effect of high injection pressure on heat release decreased. Flame separation was found to occur at high injection pressures. It was observed that the flame separation caused by the strong spray momentum was beneficial for reducing soot generation owing to the greater fuel-air interaction area. The spray and combustion processes were investigated in detail, and the significant effects of different injection pressures and injection intervals on combustion performance with the split injection method were highlighted.